Approval of unit rate of non-schedule item for supplying, fabrication and installation of study nook work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of unit rate for special shaped planter cum bench of Brac University new campus project.